2(7+3m)=5(2m-3)-m

Simple and best practice solution for 2(7+3m)=5(2m-3)-m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7+3m)=5(2m-3)-m equation:



2(7+3m)=5(2m-3)-m
We move all terms to the left:
2(7+3m)-(5(2m-3)-m)=0
We add all the numbers together, and all the variables
2(3m+7)-(5(2m-3)-m)=0
We multiply parentheses
6m-(5(2m-3)-m)+14=0
We calculate terms in parentheses: -(5(2m-3)-m), so:
5(2m-3)-m
We add all the numbers together, and all the variables
-1m+5(2m-3)
We multiply parentheses
-1m+10m-15
We add all the numbers together, and all the variables
9m-15
Back to the equation:
-(9m-15)
We get rid of parentheses
6m-9m+15+14=0
We add all the numbers together, and all the variables
-3m+29=0
We move all terms containing m to the left, all other terms to the right
-3m=-29
m=-29/-3
m=9+2/3

See similar equations:

| (x+2)÷6=(2x-10)÷8 | | -1-4x=6x+5 | | 4=f/2—-3 | | Y=2x+4=42-7x | | 5h+3h=8 | | 3b+10=56 | | 3(3x-+5)-4x=3x-10 | | 5+6x=-2x+10-45 | | 4(2x+1)=22+3 | | 9p+3+6p=-16+14p | | -(x+7)=-23 | | 7r+6=4r | | 6d−–3=21 | | 14-2y=5y | | 1/4p-6=5 | | 3(x+8)=2(2x+7) | | 2+-z=7 | | 3.2x(2.3–0.5)= | | -55+3x=85-x | | 12−0.8(x+15)=0.4x+6 | | -7x-5=-10x+26 | | 2x3-3x2=0 | | 14x-31=12x+47 | | 2x+39+1+90=180 | | 10x=560 | | 6x-9-9x=15+4x-3x | | –2u−7=–u | | (x+40)+(3x-80)=180 | | 12x-29=10x-19 | | 5+3|10−4x|=20 | | 2(x-1)+6=3+2x-10 | | 10+10+d+d=10d |

Equations solver categories